Investigating the Characteristics of Pulverized Coal Combustion Using Ansys Fluent: A CFD Study of a 300 kW Swirl Burner - Thanaporn Lertanan; Visaruta Podjanasatja; Donlaya Chuchan; Yanin Sukjai (Journal of Combustion)
Although the global focus is shifting towards clean energy to replace coal, an immediate technological transition is not yet feasible due to the widespread prevalence of the existing coal combustion technology. The main objective of the present work is to investigate the characteristics of pulverized coal combustion by using Ansys Fluent. This study describes the fluid flow and combustion reactions in the 2D axisymmetric computational fluid dynamics (CFD) model for the 300 kW cylindrical swirl pulverized coal burner. The study was conducted to analyze the combustion process including the volatilization and char combustion models, while varying the ratio of air inlet velocity, and examining the effect of swirl number on pulverized coal combustion. The numerical modeling results for burner's operating conditions are validated with the steady-state temperature measurement in the burner. The significant outcome of the associated parameters found that the flame in the burner formed a spiral before converging into the flame line in the main combustion chamber. As a result, increasing the primary airflow rate led to a decrease in the axial temperature in the preliminary combustion chamber and decreasing the primary airflow showed the highest temperature in all three cases. While the secondary airflow increases, the swirling flow will be induced inside the chamber, which affects the highest temperature profile in the preliminary combustion chamber. Changing the tertiary airflow rate did not significantly affect the combustion. However, increasing the tertiary airflow rate improved the completeness of combustion. The swirl numbers also influenced the phenomena of combustion, the volatile released, and combustion reactions which could occur more rapidly with a higher swirl number due to a higher concentration of vortex region. Similarly, the highest swirl numbers resulted in the lowest excess O2 at the exit and the least amount of CO formation.